2006
DOI: 10.1016/j.ejcts.2006.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of stroke in patients undergoing coronary bypass grafting: statins are protective☆

Abstract: To our knowledge, this is the first real-world observational report highlighting the interest of statins for the prevention of stroke in the very special situation of CABG. Even though according to randomized trials coronary patients have a benefit from these drugs, a special level of interest should be directed towards those presenting the above-mentioned risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Prior observational studies have yielded conflicting results on the impact of pre-CABG statin use on the incidence of postoperative stroke, mortality, MI, and atrial fibrillation. 22,24,[32][33][34] One study 20 reported a 30% reduction in morbidity and 50% reduction in mortality among patients taking statins prior to a variety of cardiac surgical procedures. In a study of patients undergoing isolated CABG with cardiopulmonary bypass, the investigators 21 reported a 50% reduction in 30-day mortality among patients using statins preoperatively but no reduction in the rates of stroke or MI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior observational studies have yielded conflicting results on the impact of pre-CABG statin use on the incidence of postoperative stroke, mortality, MI, and atrial fibrillation. 22,24,[32][33][34] One study 20 reported a 30% reduction in morbidity and 50% reduction in mortality among patients taking statins prior to a variety of cardiac surgical procedures. In a study of patients undergoing isolated CABG with cardiopulmonary bypass, the investigators 21 reported a 50% reduction in 30-day mortality among patients using statins preoperatively but no reduction in the rates of stroke or MI.…”
Section: Resultsmentioning
confidence: 99%
“…In a prior study of stroke after CABG, 24 the incidence of stroke among statin users was 0.88% (4/455) compared to 3.10% (11/355) among nonusers. Applying these estimates to sample size calculations, the inclusion of 854 subjects in each group (statin users vs nonusers) would provide 95% power to detect a significant difference in the incidence of stroke with an alpha value of 0.05.…”
Section: Sample Size Estimatesmentioning
confidence: 99%
“…Several nonrandomized, retrospective studies have noted an association between preoperative statin use and reduced rates of postoperative nonfatal MI and death (553,555,(557)(558)(559). In addition, preoperative statin use has been associated with reduced rates of postoperative atrial fibrillation (AF) (571,572), neurological dysfunction (555,573,574), renal dysfunction (575), and infection (576). Untreated hyperlipidemic patients have been shown to have a higher risk of post-CABG events than that of treated hyperlipidemic patients and those with normal serum lipid concentrations (567).…”
Section: Timing Of Statin Use and Cabg Outcomesmentioning
confidence: 99%
“…[99][100][101][102] Through antisympathetic activity and the stabilization of ion channels, 103 both randomized and observational studies have illustrated that statin treatment significantly reduces the risk of AF after CABG both in the perioperative period and long term after surgery. [104][105][106][107][108][109][110] Although selection bias cannot be excluded, several nonrandomized, retrospective studies have noted significant associations between perioperative statin use and a lower risk of postoperative renal dysfunction, 111,112 infection, 113 stroke, [114][115][116] and mortality, 111,[116][117][118] even among patients without elevated lipid profiles before surgery. 119 Some investigators have suggested that preoperative statin treatment may reduce the risk of mortality late after surgery, 117,[120][121][122] but it is also possible that preoperative statin administration simply predicts those who will receive statins after surgery, 123 ultimately leading to improved long-term outcomes.…”
Section: Antithrombotic Therapymentioning
confidence: 99%